The antecedents of purchase decision for hijab fashion products - Achmad Yanu Alif Fianto (Faculty of Economics and Business Mulawarman University, 2020)
The aim of this research is examining the effect of product quality, competitive price, brand image and brand consciousness on purchase decisions either partially or simultaneously. The population in this study were all women living in Jakarta, Bandung, and Surabaya who had purchased hijab products from various product lines. While the samples in this study were some women who lived in 3 metropolitan cities who had purchased hijab products from various product lines. The number of samples in this study consisted of 230 respondents. Purposive sampling technique were employed and the results of this study indicate that product quality, competitive price, brand image, and brand consciousness have a positive and significant effect on the purchase decision both partially and simultaneously. The implication of this study is recommend that marketers must be able to improve product quality because it has the biggest influence on purchasing decisions.